Choice of loading conditions of the power tram electric equipments - Зубенко, Денис Юрьевич; Габелія, Медеа Гураміївна (Eastern-European Journal of Enterprise Technologies, 2010)
On the basis of the executed researches is considered influence of service conditions on modes of a rolling stock motion. The received functional dependences have laid down in a basis of the new approach of a choice of loading conditions the power equipment of trams.